ONE STAGE RESECTION OF SIGMOID VOLVULUS: AN EXPERIENCE OF 50 CASES - Aslam, Viqar; Khan, Muhammad Abid; Bilal, Muhammad; Abidin, Zain ul (Journal of Postgraduate Medical Institute, 2011)
Objective: to assess the out come of one stage resection and primary anastomosis without intraoperative colonic lavage in patients with acute sigmoid volvulus. Material and Methods: A prospective, descriptive study was carried out in the Surgical department of Lady Reading Hospital, Peshawar from Jan 2002 to Dec 2003. Fifty patients with sigmoid volvulus were included in the study. Patients with serious co morbidity, hemodynamic instability, gangrenous or compound volvulus on laparotomy were excluded from the study. All the patients were assessed and operated upon by a senior surgeon. Resection of the sigmoid colon and primary anastomosis was done after only manual decompression in all cases. The demographic data, clinical features, radiologic and operative findings, out come of the procedure in terms of postoperative complications and duration of hospital stay were recorded on a proforma. The data was entered and processed on the SPSS 10 version. Results: The patients included 44 males and 6 females. Male to female ratio was 7.3:1. Mean age was 57 years. Most frequent clinical features were abdominal pain, distension and constipation. Postoperatively, superficial wound infection was seen in 14% patients (n=7), transient paralytic ileus in 22% cases (n=11). Pulmonary complications occurred in 6% patients (n=3). No deaths or clinical anastomotic leak occurred. Duration of hospital stay ranged from 6-17 days (mean 11 days). Conclusion: Resection of sigmoid colon primary anastomosis can safely be carried out without on-table colonic lavage in selected patients with viable colon.